A CRITICAL DISCOURSE ANALYSIS OF RMâ€™S SPEECH - Uswatun Hasanah; Alek Alek; Didin Nuruddin Hidayat (Jurnal Humaniora Teknologi, 2019)
This research explores critical discourse analysis of a speech conveyed by RM, the leader of BTS on Monday noon, 24th September 2018 in United Nations Assembly on the inauguration of UNICEFâ€™s new global partnership â€œGeneration Unlimitedâ€. The framework of analysis was based on M.A.K Halliday theory namely Systematic Functional Grammar (SFG) includes analysis of transitivity and modality. This CDA study intended at revealing the language, ideology and power which involved in RMâ€™s six-minute speech in order to convincea audiences to agree and approve his ideas related to the issue of empowering young people in education, training and employment. The data was collected from a six-minute speech by RM and analyzed qualitatively. The speech consisted of 784 words that constituted on 47 sentences. The result of the analysis showed that all processes types of transitivity system found in the speech with relational process as the most dominant process, followed by mental process in the second rank and behavioral process in the next rank. In addition, modality analysis result showed that the general tense use in the speech were simple present and simple past with the first and second pronoun as the participants, none of singular third person used in the speech. Last, May and Will took more often used in the speech compare with other modal auxiliaries.